The Design, Construction, and Expert Appraisal of A 220v Inverter - Omotayo Olabo Obielodan; Amos Ochayi Onojah; Olayinka Blessing Iyiola; Adenike Aderogba Onojah; Simon Ayoola Taiwo (Universitas Pendidikan Indonesia (UPI), 2021)
This project is about the design and construction of a 220 volts inverter at a frequency of 50Hz. The device is constructed with locally sourced components and materials of regulated standards. The basic principle of its operation is a simple conversion of 12V DC from a battery using integrated circuits and semiconductors at a frequency of 50Hz, into a 220V AC across the windings of a transformer. A battery charger is used to charge the battery using an intelligent digital display charger. This project (device) offers a better alternative to Public Power Supply, Generators as well as UPS considering it is cost-effective, noiseless, and easy maintainability. It was concluded that the inverter was constructed with considerable cost, available and reliable components rather than the more exorbitant unavailable ones. It was however recommended that the Government at various levels should encourage engineering practice by financing and training engineering within and outside the country for the benefit of the students and the nation at large.